2016
DOI: 10.1002/mnfr.201500744
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte linoleic acid, but not oleic acid, is associated with improvements in body composition in men and women

Abstract: Scope Supplementation with linoleic acid (LA; 18:2Ω6)-rich oils increases lean mass and decreases trunk adipose mass in people. Erythrocyte fatty acids reflect the dietary pattern of fatty acid intake and endogenous metabolism of fatty acids. The aim of this study is to determine the relationship of erythrocyte LA, with aspects of body composition, insulin resistance and inflammation. Additionally, we tested for relationships of oleic acid (OA) and the sum of long chain omega-three fatty acids (LC-Ω3-SUM), on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Nonetheless, increasing MUFA occurs both at the expense of decreasing PUFA (specifically ALA) and decreasing SFA. One recent study showed that erythrocyte linoleic acid was associated with decreased trunk fat mass in men and women . In conjunction with our finding, this suggests that varying PUFA (LA vs. ALA) may have a different effect on android fat mass.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, increasing MUFA occurs both at the expense of decreasing PUFA (specifically ALA) and decreasing SFA. One recent study showed that erythrocyte linoleic acid was associated with decreased trunk fat mass in men and women . In conjunction with our finding, this suggests that varying PUFA (LA vs. ALA) may have a different effect on android fat mass.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with reports in adults, 38,39 we demonstrated that proportions of EPA + DHA in RBC are a useful biomarker to reflect dietary EPA, DHA and fish servings in children with obesity. Other fatty acids in RBC including oleic acid were explored and did not relate to any of the measures of adiposity as has been observed in other studies 40,41 . It is noteworthy that due to possible differences in fatty acids extraction methods and analytic procedures, the range of EPA + DHA in this study appeared to be lower than previously reported 42 .…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, although many of these studies report weight gain and increased adipose inflammation, the final outcome is highly dependent on the whole diet and other external factors such age or physical activity. Some research even showed that dietary supplements with C18:2 increase lean mass 26 . In our study with pigs none of the carcass traits analyzed were affected by the higher FADS2 activity of the A rs321384923 allele.…”
Section: Discussionmentioning
confidence: 99%